Jack en Jill - Torres, Mar S.; Sampaguita Pictures (Unico Entertainment, 2005)
Sibling Luisa (Lolita Rodriguez) and Goryo (Dolphy) play twisted roles : she drives a jeepney, he does all the household chores; she gets into brawls with men, he prefers to be call 'Glory'. All these they do in support of their father. Mang Ambo, a driver for the rich and reckless Gardo (Rogelio De La Rosa), son of the elite Don Pepito (Horacio Morales) and Dona Teresita (Etang Discher). When Mang Ambo's health fails him, he introduces Luisa to the family, disguised as a boy named Itoy. Goryo on the other hand, runs away to look for a job and end up being taken in - and mistaken for an actual girl by Dona Teresita as her own 'daughter'. Living in totally new circumstances and with each bearing the secret of the other, how long can they keep up playing their game?